2009
DOI: 10.2147/btt.s3663
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance treatment with infliximab for the management of Crohn’s disease in adults

Abstract: Crohn's disease (CD) is a chronic, relapsing disease, the continuous cycle of which deeply affects the long-term course which, eventually, leads to fi brosis and development of transmural complications. It is well known that CD is an immune-mediated clinical condition and that tumor necrosis factor-α (TNF-α) plays a fundamental role in the pathogenesis of the disease. Current clinical guidelines recommend that patients with mild to moderate active CD should be treated initially with corticosteroids. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…There is evidence that scheduled treatment with IFX not only results in improved efficacy 69 compared with episodic treatment, but that this is associated with a reduced level of immunogenicity. 70 Clinicians should also consider administering a loading dose of a biologic at the commencement of therapy, because, in addition to achieving therapeutic levels rapidly, this has been reported to reduce immunogenicity, 71 as has intravenous hydrocortisone treatment immediately prior to infusion with IFX. 72 Potential limitations of the present study include the diversity of study design, patient populations, disease severity, concomitant therapies, assay methods and timing of the studies reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that scheduled treatment with IFX not only results in improved efficacy 69 compared with episodic treatment, but that this is associated with a reduced level of immunogenicity. 70 Clinicians should also consider administering a loading dose of a biologic at the commencement of therapy, because, in addition to achieving therapeutic levels rapidly, this has been reported to reduce immunogenicity, 71 as has intravenous hydrocortisone treatment immediately prior to infusion with IFX. 72 Potential limitations of the present study include the diversity of study design, patient populations, disease severity, concomitant therapies, assay methods and timing of the studies reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…9 It has been recently shown that patients suffering from nonfistulizing perianal CD may develop anal abscesses under treatment with infliximab. 8,10 But our patient did not suffer from perianal disease in the first appearance of the disease, and perianal disease appeared when she was under treatment with infliximab (and under sustained remission). This type of complication is quite surprising.…”
mentioning
confidence: 69%
“…Infliximab is effective in obtaining and maintaining remission of CD, 8 and the safety profile has been confirmed by a recent retrospective study showing a rate of serious adverse events lower than 10%. 9 It has been recently shown that patients suffering from nonfistulizing perianal CD may develop anal abscesses under treatment with infliximab.…”
mentioning
confidence: 83%
“…In addition to these observations are the approaches for scheduling treatment with infliximab that lead to improved efficacy and reduced immunogenicity compared to episodic treatment [77,78]. Bots et al, (2021) demonstrated reduced rates of anti-drug antibodies in IBD patients treated with combination therapy consisting of infliximab (RR 0.52), adalimumab (RR 0.31), golimumab (RR 0.29), certolizumab pegol (RR 0.30), and natalizumab (RR 0.20) [39].…”
Section: Strategies For Precise Detection and Preventing Immunologica...mentioning
confidence: 99%